CA19.9 Serum Level Predicts Lymph-Nodes Status in Resectable Pancreatic Ductal Adenocarcinoma: A Retrospective Single-Center Analysis - Coppola, Alessandro; La Vaccara, Vincenzo; Fiore, Michele; Farolfi, Tommaso; Ramella, Sara; Angeletti, Silvia; Coppola, Roberto; Caputo, Damiano (Frontiers in Oncology, 2021)
Background: The choice between upfront surgery or neoadjuvant treatments (NT) for resectable pancreatic ductal adenocarcinoma (R-PDAC) is controversial. R-PDAC with potential nodal involvement could benefit from NT. Ca 19.9 and serum albumin levels, alone or in combination, proved their efficacy in assessing PDAC prognosis. This study aimed to verify Ca 19.9 serum levels in predicting nodal status in R-PDAC. Methods: Preoperative Ca 19.9, as well as albumin, serum levels of 165 patients selected to upfront surgery have been retrospectively collected and correlated to pathological nodal status, resection margins status (R), and vascular resections (VR). We further performed ROC curve analysis to identify optimal Ca 19.9 cut-off for pN+, R+, and vascular resection prediction. Results: Increased Ca 19.9 levels in 114 PDAC patients were significantly associated with pN+ (p < 0.001). This ability, confirmed in all the series by ROC curve analysis (Ca 19.9 ≥32 U/ml), was lost in presence of hypoalbuminemia. Furthermore, Ca 19.9 at the cut-off>418 U/ml was significantly associated with R+ (87% specificity, 36% sensitivity, p 0.014). Ca 19.9, at the cut-off>78 U/ml, pointed a trend to significance to predict VR's need (sensitivity 67%, specificity 53%; p= 0.059). Conclusions: In R-PDAC with normal serum albumin levels, Ca 19.9 predicts pN+ and R+, thus suggesting a crucial role in deciding on a neoadjuvant treatment.